A New Era in Preschool Education: The Effects of COVID-19 on Children and on the Pedagogical Practice - Varga, László; Németh, Krisztina (Journal of Cultural Analysis and Social Change, 2026)
The COVID-19 pandemic triggered changes that continue to impact the everyday practice of preschool education and the physical and psychological well-being of children. More than five years have passed since the start of the 2020 pandemic; therefore, beyond the description of the acute crisis period, the study outlines post-pandemic phenomena from the viewpoint of preschool teachers. Between July 1 and 30, 2025, 100 preschool teachers completed an anonymous, online questionnaire as part of this research. The questionnaire included closed-ended questions, multiple choice questions, Likert scale statements, and open-ended questions that focused on children’s somatic symptoms (e.g. fatigue, sleep disturbances, headaches), psychological and behavioural problems (anxiety, disengagement, increased need for attention), and the changes in pedagogical practice and cooperation with parents. The majority of participants reported a decline in their sense of security and autonomy, a more frequent onset of somatic and psychological symptoms in children, growing complexity of pedagogical work, and increasing challenges in cooperating with parents. The study highlights the multidimensional challenges of post-COVID early childhood education and emphasises the need for psychosocial supporting systems and the conscious strengthening of preschool–family partnerships to promote children’s healthy development.